Power generation using rice husk derived fuels from CO2-assisted catalytic pyrolysis over Co/Al2O3. (1st September 2020) - Jung, Sungyup; Kwon, Dohee; Park, Young-Kwon; Lee, Kyun Ho; Kwon, Eilhann E.
Abstract: The new energy conversion platform for CO2 /biomass waste into syngas was constructed through pyrolysis of rice husk to achieve two goals: (1) energy production and (2) CO2 reduction. First part of this study involves a fundamental understanding of effectiveness of CO2 on syngas production experimentally. In the presence of CO2, gas phase reactions between CO2 and volatile organic compounds, evolved from rice husk pyrolysis, led to CO formation. The improvement of syngas generation was achieved through additional thermal energies and catalytic pyrolysis. The second part evaluated theoretical power generations from an ideal turbine cycle using rice husk derived fuels (syngas and hydrocarbon mixtures). Different H2 /CO ratios obtained from various pyrolysis and purge gas conditions (N2 /CO2 ratio) had influence on the stoichiometric fuel to air ratio, lower heating value, and specific heat of rice husk fuels. This resulted in the variation of power generation performances. The power generations from rice husk fuels were up to 1.5 times higher than those from natural gases when fed into the turbine cycle with fixed amount of air. Both experimental and theoretical results suggest that this renewable platform for syngas production could be a considered sustainable way for waste valorizations and energy productions. Highlights: A sustainable platform for rice husk/CO2 to energy was constructed. Multi-stage and catalytic pyrolysis enhanced more syngas formation. CO2 purge gas contributed to more CO generation via gas phase reaction with VOCs. Co catalyst improved dehydrogenation (H2 production). 1.5x higher power generation of rice husk fuel was shown comparing to natural gases.